Synergistic Nanomedicine: Passive, Active, and Ultrasound-Triggered Drug Delivery in Cancer Treatment - Elkhodiry, Mohamed A. (2015)
Nanocarriers are heavily researched as drug delivery vehicles capable of sequestering antineoplastic agents and then releasing their contents at the desired location. The feasibility of using such carriers stems from their ability to produce a multimodel delivery system whereby passive, ligand and triggered targeting can be applied in the fight against cancer. Passive targeting capitalizes on the leaky nature of tumor tissue which allows for the extravasation of particles with a size smaller than 0.5 m into the tumors. Ligand targeting utilizes the concept of receptor-mediated endocytosis and involves the conjugation of ligands onto the surface of nanoparticles, while triggered targeting involves the use of external and internal stimuli to release the carriers contents upon reaching the diseased location. In this review, micelles and liposomes have been considered due to the promising results they have shown in vivo and in vitro and their potential for advancements into clinical trials. Thus, this review focuses on the most recent advancements in the field of micellar and liposomal drug delivery and considers the synergistic effect of passive- and ligand-targeting strategies, and the use of ultrasound in triggering drug release at the tumor site.